Primary Splenic Torsion Associated with Accessory Spleen in a Dog - dos Santos, Bruna Santos; Gomes, Cristiano; Camargo, Jéssica Francielle; Trindade Gerardi, Anelise Bonilla; Gouvea, Aline da Silva; Driemeier, David; Contesini, Emerson Antonio (Acta Scientiae Veterinariae, 2019)
Background: Primary splenic torsion occurs when there is a splenic vascular pedicle rotation without association of other diseases, as the Gastric Dilatation Volvulus (GDV). Accessory spleen consists in a splenic tissue fraction independent from main organ, caused by a spleen defect in the embryonic development, most remaining asymptomatic and discovered incidentally. They have their own blood supply, which is usually from a branch of the splenic artery. Present report represents a primary splenic torsion with the accessory spleen finding in a dog. Case: A 7-year-old female mongrel was referred to Veterinary Hospital of Universidade Federal do Rio Grande do Sul, showing pain and firm consistency in the left abdominal region, prostration and inappetence four days before the medical appointment. At the clinical examination, the patient was alert, 7% dehydration, hypocorous mucous membranes, without alteration in lymph nodes, left abdominal pain. Laboratory tests, chest radiographic and abdominal ultrasound was requested. Two images compatible with splenic image were visualized, one with a regular structure without vascularization suggesting splenic torsion and another with homogeneous parenchyma and echogenicity of the normal spleen, with vascularization signal. The animal was referred to the surgical procedure and the anesthetic induction protocol with propofol (6 mg.kg -1) and ketamine hydrochloride (2 mg.kg -1) and maintenance with total intravenous anesthesia with propofol (0.2-0.4 mg.kg -1 / min) and lidocaine (2 mg.kg -1), in a semi-closed loop and spontaneous ventilation. The pre-retro-umbilical incision in the ventral midline was performed, and the exploratory celiotomy was done. During the cavity exploring, a small amount of free fluid and a structure compatible with the spleen were observed. It was noted that the splenic vascular pedicle was twisted around its axis and the gastroesplenic and splenocolic ligaments were also involved. The stomach maintained its position, size and vascularization. Thus, an isolated or primary splenic torsion was characterized. The exploratory laparotomy was recommended, and the total splenectomy was the treatment of choice. The accessory spleen did not demonstrate vascular damage; therefore, was advocated the zeal in handling to preserve your integrity. Discussion: Isolated splenic torsion is a rare occurrence in dogs. A retrospective study was performed with 60 dogs presenting with non-traumatic hemoperitoneum, in which only three cases presented splenic torsion. Usually, twisting occurs in large or giant breed dogs with deep chest conformation. The etiology of splenic torsion is not well established. Primary splenic torsion is considered emergency surgery, and the prognosis is considered favorable. The literature shows no relation between the presence of the accessory spleen and the occurrence of primary splenic torsion, but both occur due to congenital defects, both of which may be correlated in this case. The accessory spleen is characterized by a defect in the embryonic formation of the splenic tissue and may be associated with other congenital malformations. It can be concluded that in the primary splenic torsion, early surgical treatment is the most indicated. Total splenectomy was considered adequate, and preservation of the accessory spleen was important due to the possibility of some organ functionality.